2020
DOI: 10.1111/cogs.12822
|View full text |Cite
|
Sign up to set email alerts
|

Word Order Typology Interacts With Linguistic Complexity: A Cross‐Linguistic Corpus Study

Abstract: Much previous work has suggested that word order preferences across languages can be explained by the dependency distance minimization constraint (Ferrer-i Cancho, 2008Hawkins, 1994). Consistent with this claim, corpus studies have shown that the average distance between a head (e.g., verb) and its dependent (e.g., noun) tends to be short cross-linguistically show that the comprehension system can adapt to the typological properties of a language, for example, verb-final order, leading to more complex structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 88 publications
4
36
0
Order By: Relevance
“…The results show that comprehension/production efficiency based factors affect dependency distance and ordering of preverbal dependents in Hindi. Previous work investigating dependency distance has demonstrated that SOV languages allow for longer dependency distance between the verb and its prior dependents (Futrell et al, 2020c;Yadav et al, 2020;Konieczny, 2000). The current work makes an important contribution by highlighting that compared to preverbal adjuncts, the core arguments (subject, indirect object and direct object) tend to be closer to the verb in an SOV language like Hindi.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results show that comprehension/production efficiency based factors affect dependency distance and ordering of preverbal dependents in Hindi. Previous work investigating dependency distance has demonstrated that SOV languages allow for longer dependency distance between the verb and its prior dependents (Futrell et al, 2020c;Yadav et al, 2020;Konieczny, 2000). The current work makes an important contribution by highlighting that compared to preverbal adjuncts, the core arguments (subject, indirect object and direct object) tend to be closer to the verb in an SOV language like Hindi.…”
Section: Discussionmentioning
confidence: 99%
“…Morphological marking A feature of a majority of head-final languages is the presence of case marking on nouns that signifies the syntactic relation between a nouns and its verbal head. 2 Crosslinguistically, the presence of case-markers has been shown to increase the dependency distance between a nominal and its verbal head (e.g., Yadav et al, 2020), perhaps because nominal casemarkers help in making robust predictions about upcoming verbs, as shown by . Therefore, we predict that nominals with case marking should be farther out from the verb than those without.…”
Section: Head-dependent Mutual Information (Hdmi)mentioning
confidence: 99%
“…this pattern also comes from a recent cross-linguistic corpus study by Yadav et al (2020) who show that the number of intervening heads is very constrained across languages, and this constraint shows less variability compared to number of intervening words (see, Figures 11,12).…”
Section: Measuring Syntactic Complexitymentioning
confidence: 56%
“…Given the limited memory resource, it is reasonable to assume that more structure building in the intervening region should lead to more difficultly in processing the unresolved dependency. Consistent with this idea, there is evidence that not only the number, but the complexity of the words that intervene a syntactic dependency matters (e.g, Wasow, 2002;Wasow & Arnold, 2003;Yadav, Vaidya, Shukla, & Husain, 2020). This line of work predicts that the complexity of the linguistic material that intervenes a syntactic dependency will be minimized.…”
Section: A Reappraisal Of Dependency Length Minimizationmentioning
confidence: 94%
See 1 more Smart Citation